2013
DOI: 10.1017/jns.2013.6
|View full text |Cite
|
Sign up to set email alerts
|

Development of the gut microbiota in southern Indian infants from birth to 6 months: a molecular analysis

Abstract: Acquisition of the gastrointestinal microbiota at birth may have long-term health impacts. We longitudinally characterised major microbial communities in the faeces of a cohort of infants using molecular methods. Faecal samples were prospectively obtained at several time points after birth from eighty-three infants. Real-time PCR using SYBR green and primers targeted at 16S rRNA gene sequences were used to quantify Bifidobacterium, Lactobacillus acidophilus group, Bacteroides–Prevotella group, Enterobacteriace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 36 publications
4
59
0
1
Order By: Relevance
“…Several studies have found that the colonization of Lactobacillus, Bifidobacterium, and Bacteroides is delayed or completely absent in infants born via C-section (92,96,106,107) and the lack of exposure to vaginally-derived Lactobacillus species can lead to differences in microbial succession. Subsequent diversity for the major phyla of gut microbiota-Actinobacteria (dominated by Bifidobacterium), Bacteroidetes, and Proteobacteria-is also significantly lower in C-section-delivered infants (92,(107)(108)(109)(110)(111)(112).…”
Section: Birth Methods and Its Role In Gut Microbiota Modulationmentioning
confidence: 98%
“…Several studies have found that the colonization of Lactobacillus, Bifidobacterium, and Bacteroides is delayed or completely absent in infants born via C-section (92,96,106,107) and the lack of exposure to vaginally-derived Lactobacillus species can lead to differences in microbial succession. Subsequent diversity for the major phyla of gut microbiota-Actinobacteria (dominated by Bifidobacterium), Bacteroidetes, and Proteobacteria-is also significantly lower in C-section-delivered infants (92,(107)(108)(109)(110)(111)(112).…”
Section: Birth Methods and Its Role In Gut Microbiota Modulationmentioning
confidence: 98%
“…Postnatal colonization of the neonatal intestine by Bacteroides and Bifidobacterium spp. is also delayed in babies delivered by C-section [7476] and these babies have higher levels of intestinal Clostridium difficile [7780]. While it remains unknown how long the differences in microbial composition introduced by delivery mode persist in the infant, differences in specific microbial species have been observed between C-section- and vaginally delivered babies after 1 month [81], 2 years [82], and even 7 years [83] of life.…”
Section: Disruptors Of the Colonization And Development Of The Neonatmentioning
confidence: 99%
“…In addition, Huurre et al [20] showed that infants born by Csection harbored lower amounts of total bacteria in their guts at 1 month of age, mainly due to a reduced number of bifidobacteria. Underrepresentation of Bacteroides is also frequently detected in the microbiota of C-section infants surveyed at 3-4 months of age [16,19,[21][22][23]. Longer term studies that have followed microbiota composition in infants during the first 2 years of life have confirmed an association of C-section with delayed colonization of the Bacteroidetes phylum, and with lower total microbial diversity up to 2 years of age [22,24].…”
Section: Altered Exposure To Microbes At Birth and Different Gut Colomentioning
confidence: 95%